VIDEOGAMES IN RELATIONSHIP CONFLICTS - Butt, Mahli-Ann (AoIR Selected Papers of Internet Research, 2023)
This paper contributes to feminist games studies, media studies, and internet studies, presenting findings from semi-structured interviews conducted with seven self-identified women who played videogames with their romantic partners. It seeks to develop a more multifaceted understanding of women’s gaming ‘lifeworlds’ and their struggles to participate and ‘stay in’ the male-dominant public. Specifically, this study observes how relationship dynamics and romantic ties between couples can play an important role in shaping women’s gaming practices. In doing so, this argument challenges the assumption that women’s play can be given as simply ‘a free choice’. Exploring conflicts between couples relative to their gaming habits, as I examine, demonstrates how the accounts of women’s evolving (dis)engagement to gaming cannot sufficiently be captured within a scope that is often limited to discussions about women’s barriers to entry.